Personality traits and stress levels among senior dental students: Evidence from Malaysia and Singapore - Mohd Yusof, Zamros Yuzadi; Wan Hassan, Wan Nurazreena; Razak, Ishak Abdul; Hashim, S.M.N.; Tahir, M.K.A.M.; Keng, S.B. (Seameo Regional Tropical Medicine & Public Health, 2016)
This study aimed to evaluate the association between dental students’ personality traits and stress levels in relation to dental education programs among senior dental students in University Malaya (UM) in Malaysia and National University of Singapore (NUS). A cross-sectional survey using a self-administered questionnaire was conducted on UM and NUS senior dental students. The questionnaire comprised items on demographic background, the Big Five Inventory Personality Traits (BFIPT) test and a modified Dental Environment Stress (DES) scale. Rasch analysis was used to convert raw data to interval scores. Analyses were done by t-test, Pearson correlation, and Hierarchical regression statistics. The response rate was 100% (UM=132, NUS=76). Personality trait Agreeableness (mean=0.30) was significantly more prevalent among UM than NUS students (mean=0.15, p=0.016). In NUS, Neuroticism (mean=0.36) was significantly more prevalent than in UM (mean=0.14, p=0.002). The DES mean score was higher among NUS (mean=0.23) than UM students (mean=0.07). In UM, Neuroticism was significantly correlated with stress levels (r=0.338, p<0.001). In NUS, these were Neuroticism (r=0.278, p=0.015), Agreeableness (r=0.250, p=0.029) and Conscientiousness (r=-0.242, p=0.035) personality traits. The correlation was strongest for personality trait Neuroticism in both schools. Hierarchical regression analysis showed that gender and Neuroticism were significant predictors for students’ stress levels (p<0.05) with the latter exerting a bigger effect size (R2=0.18) than gender (R2=004). This study showed that gender and Neuroticism personality trait were significant predictors for stress levels among selected groups of dental students in Southeast Asia. Information on students’ personality may be useful in new students’ intake, stress management counseling and future program reviews.